EFEKTIVITAS MEDIA KOMIK PADA MATERI SIFAT-SIFAT BANGUN RUANG UNTUK SISWA KELAS V SD NEGERI 6I KOTA BENGKULU - Kurniati, Desi; Rahimah, Dewi; Rusdi, Rusdi (JP2MS, 2017)
AbstractThe study aimed to describe the level of effectiveness of the comic media on the subjects of the three dimentionals characters for Student’s Grade V SD Negeri 61 Kota Bengkulu. The research type is research development. Effectiveness was tested on 30 students of grade VB SD Negeri 61 Kota Bengkulu even semester of academic year 2016/2017. The indicators of effectiveness of comic media seen from the criteria of student activity in learning activities, criteria of student response to learning and average learning outcomes. The results showed that the comics developed were categorized effective with the achievement of effectiveness: (1) Active student activity with average score of student activity 3,93; (2) Student response to the learning process is very good with an average score of 4,05; (3) The result of student learning VB SD Negeri 61 Kota Bengkulu effective with the completeness of learning classical students reach 76,67 % and the average value of 79,31.Keywords: Development Research, Comic Media, Math Lesson.